2004
DOI: 10.1038/sj.onc.1208174
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase inhibitors are chemopreventive for mammary cancer in neu-N transgenic mice

Abstract: High levels of fatty acid synthase (FAS) have been found in cancer precursor lesions of the colon, stomach, esophagus, oral cavity, prostate, and breast. Inhibition of FAS with C75 has led to a significant antitumor effect in both human breast and prostate cancer xenografts. Recently, HER2/neu, which has also been identified in preneoplastic breast lesions, has been shown to regulate FAS expression through the PI3K/Akt signal transduction pathway rendering them susceptible to FAS inhibition. Utilizing the neu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 33 publications
1
114
0
3
Order By: Relevance
“…For instance, it has been shown that C75 has anti-tumor activity in xenograft models of breast, 48 lung, 49 prostate 50 and renal 51 cancers, and it prevents breast cancer formation in HER2 transgenic mice. 52 TVB-2640 is the most recent orally available FASN inhibitor. It is currently in phase I clinical trial for the treatment of solid tumors (https://clinical trials.gov/ct2/show/NCT02223247).…”
Section: Fasn Is Required For Akt and Akt/c-met Driven Hepatocarcinogmentioning
confidence: 99%
“…For instance, it has been shown that C75 has anti-tumor activity in xenograft models of breast, 48 lung, 49 prostate 50 and renal 51 cancers, and it prevents breast cancer formation in HER2 transgenic mice. 52 TVB-2640 is the most recent orally available FASN inhibitor. It is currently in phase I clinical trial for the treatment of solid tumors (https://clinical trials.gov/ct2/show/NCT02223247).…”
Section: Fasn Is Required For Akt and Akt/c-met Driven Hepatocarcinogmentioning
confidence: 99%
“…7,8,24 Moreover, the inhibition of FASN activity is chemopreventive in the neu-N mouse model for breast cancer. 25 The biological mechanisms responsible for the FASN inhibition-induced apoptosis are still not clear. The extrinsic pathway of apoptosis triggered by death domains was described in breast cancer cells because of the accumulation of malonyl-CoA and ceramide after FASN silencing with siRNA.…”
mentioning
confidence: 99%
“…Antineoplastic activity, without anorectic effects, can be achieved with this drug by selective pharmacologic inhibition of FAS without stimulation of CPT1, and we demonstrated effective treatment of mice bearing xenografts of the Colo680N squamous cell esophageal cancer cell line using this drug (figure4). Other animal experiments have also found C93 to work well for treatment of cancer xenografts in a variety of other tumor types [98,[109][110][111][112], and encouraging results have been seen in cancer chemoprevention experiments [113,114]. …”
Section: Fig 1 Fas Expression In Scc and Eacmentioning
confidence: 99%